Can deep transcranial magnetic stimulation (DTMS) be used to treat substance use disorders (SUD)? A systematic review - Kedzior, Karina Karolina (BMC Psychiatry, 2018)
BACKGROUND: Deep transcranial magnetic stimulation (DTMS) is a non-invasive method of stimulating widespread cortical areas and, presumably, deeper neural networks. The current study assessed the effects of DTMS in the treatment of substance use disorders (SUD) using a systematic review. METHODS: Electronic literature search (PsycInfo, Medline until April 2017) identified k = 9 studies (k = 4 randomized-controlled trials, RCTs, with inactive sham and k = 5 open-label studies). DTMS was most commonly applied using high frequency/intensity (10–20 Hz/100–120% of the resting motor threshold, MT) protocols for 10–20 daily sessions in cases with alcohol, nicotine or cocaine use disorders. The outcome measures were craving and dependence (according to standardized scales) or consumption (frequency, abstinence or results of biological assays) at the end of the daily treatment phases and at the last follow-up. RESULTS: Acute and longer-term (6–12 months) reductions in alcohol craving were observed after 20 sessions (20 Hz, 120% MT) relative to baseline in k = 4 open-label studies with comorbid SUD and major depressive disorder (MDD). In k = 2 RCTs without MDD, alcohol consumption acutely decreased after 10–12 sessions (10–20 Hz, 100–120% MT) relative to baseline or to sham. Alcohol craving was reduced only after higher frequency/intensity DTMS (20 Hz, 120% MT) relative to sham in k = 1 RCT. Nicotine consumption was reduced and abstinence was increased after 13 sessions (10 Hz, 120% MT) and at the 6-month follow-up relative to sham in k = 1 RCT. Cocaine craving was reduced after 12 sessions (15 Hz, 100% MT) and at the 2-month follow-up relative to baseline in k = 1 open-label study while consumption was reduced after 12 sessions (10 Hz, 100% MT) relative to baseline but not to sham in k = 1 RCT. CONCLUSIONS: High-frequency DTMS may be effective at treating some SUD both acutely and in the longer-term. Large RCTs with inactive sham are required to determine the efficacy and the optimal stimulation parameters of DTMS for the treatment of SUD.